Moral and Spiritual Values in Education : A Challenge to Every American - Bower, William Clayton, 1878-1982 (Book collections on Project MUSE., 2015)
This book deals with the multiple problem of education in the public schools as it relates to moral and spiritual values. The author cuts a wide swath through the tangled underbrush of church and state, religion and education, sacred and secular, spiritual and materialistic, ""body and soul, "" and lets in a lot of light. To these problems the author brings a lifetime of courageous reflection and experience. To them he also brings, as case studies, the actual experiences of actual children and teachers in actual classrooms in Kentucky, where an experimental program of education in moral and spi.